Exploring the space for task shifting to support nursing on neonatal wards in Kenyan public hospitals - Jacinta Nzinga; Jacob McKnight; Joyline Jepkosgei; Mike English (BMC, 2019)
Abstract Background Nursing practice is a key driver of quality care and can influence newborn health outcomes where nurses are the primary care givers to this highly dependent group. However, in sub-Saharan Africa, nursing work environments are characterized by heavy workloads, insufficient staffing and regular medical emergencies, which compromise the ability of nurses to provide quality care. Task shifting has been promoted as one strategy for making efficient use of human resources and addressing these issues. Aims and objectives We aimed to understand the nature and practice of neonatal nursing in public hospitals in Nairobi so as to determine what prospect there might be for relieving pressure by shifting nurses' work to others. Methods This paper is based on an 18-month qualitative study of three newborn units of three public hospitals-all located in Nairobi county-using an ethnographic approach. We draw upon a mix of 32 interviews, over 250 h' observations, field notes and informal conversations. Data were collected from senior nursing experts in newborn nursing, neonatal nurse in-charges, neonatal nurses, nursing students and support staff. Results To cope with difficult work conditions characterized by resource challenges and competing priorities, nurses have developed a ritualized schedule and a form of 'subconscious triage'. Informal, organic task shifting was already taking place whereby particular nursing tasks were delegated to students, mothers and support staff, often without any structured supervision. Despite this practice, nurses were agnostic about formal institutionalization of task shifting due to concerns around professional boundaries and the practicality of integrating a new cadre into an already stressed health system. Conclusion Our findings revealed a routine template of neonatal nursing work which nurses used to control unpredictability. We found that this model of nursing encouraged delegation of less technical tasks to subordinates, parents and other staff through the process of 'subconscious triage'. The rich insights we gained from this organic form of task shifting can inform more formal task-shifting projects as they seek to identify tasks most easily delegated, and how best to support and work with busy nurses.